2022
DOI: 10.1093/mnras/stac1251
|View full text |Cite
|
Sign up to set email alerts
|

WIYN open cluster study: The old open cluster, NGC 188, and a re-evaluation of Lithium-richness among red giants

Abstract: We present WIYN★/Hydra spectra of 34 red giant candidate members of NGC 188, which, together with WOCS† and Gaia data yield 23 single members, 6 binary members, 4 single nonmembers, and 1 binary nonmember. We report [Fe/H] for 29 members and derive [Fe/H]NGC188 = +0.064 ± 0.018 dex (σμ) (sky spectra yield A(Fe)⊙ = 7.520 ± 0.015 dex (σμ)). We discuss effects on the derived parameters of varying Yale-Yonsei isochrones to fit the turnoff. We take advantage of the coolest, lowest-gravity giants to refine the line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 112 publications
0
13
0
Order By: Relevance
“…It was also found that the Li abundances of a fraction of giant stars are higher than 1.5 dex, which is the traditional definition of a so-called Li-rich giant star. Although some recent researches show that this threshold is flawed (e.g., Chanamé et al 2022;Sun et al 2022), we still follow this threshold in this work. The percentage of Li-rich giant stars is around ∼1% (Brown et al 1989;Gao et al 2019;Martell et al 2021).…”
Section: Introductionmentioning
confidence: 81%
“…It was also found that the Li abundances of a fraction of giant stars are higher than 1.5 dex, which is the traditional definition of a so-called Li-rich giant star. Although some recent researches show that this threshold is flawed (e.g., Chanamé et al 2022;Sun et al 2022), we still follow this threshold in this work. The percentage of Li-rich giant stars is around ∼1% (Brown et al 1989;Gao et al 2019;Martell et al 2021).…”
Section: Introductionmentioning
confidence: 81%
“…Given that planet engulfment is not expected to decrease the carbon isotopic ratio of the star, this seems an unlikely explanation for the abundance of this particular giant. This Li-rich giant is an excellent example of why 12 C/ 13 C should definitely be considered when discussing the source of Li-enrichment and anomalous surface abundances in evolved stars (e.g., Sun et al 2022).…”
Section: Discussion: Extra Mixing In the Rgbmentioning
confidence: 99%
“…The C 12 /C 13 should definitely be considered when discussing the source of Li-enrichment and anomalous surface abundances in evolved stars (e.g., Sun et al 2022).…”
Section: Discussion: Extra-mixing In the Rgbmentioning
confidence: 99%